Efektivitas Penerapan e-RKAM sebagai Aplikasi Keuangan Madrasah Berdasarkan Pendekatan Technology Acceptance Model - Deni Hardianto; Abduloh Abduloh; Bambang Ismaya; Endi Rochaendi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Digital transformation in the governance of Islamic education faces multifaceted challenges, particularly in the context of private Islamic senior high schools (Madrasah Aliyah Swasta, MAS) operating under resource constraints. This study aims to examine the factors influencing the acceptance of the Electronic Budget and Work Plan Application for Madrasahs (e-RKAM) using a modified Technology Acceptance Model (TAM). Two external variables—user experience and training—were analyzed for their effects on perceived ease of use (PEOU) and perceived usefulness (PU), as well as their implications for user attitudes and behavioral intentions toward system utilization. Employing a quantitative approach, this study conducted path analysis using AMOS software on data collected from MAS in Karawang Regency. The findings indicate that both experience and training significantly influence PEOU and PU, which in turn shape user attitudes and behavioral intentions. The results confirm that perceived usefulness exerts the strongest influence on user attitudes, while attitude serves as the primary predictor of sustained system use. Theoretically, this study extends the applicability of TAM to mandatory technology adoption in Islamic education, while practically, it highlights the urgency of designing participatory, contextual, and experience-based training programs to enhance the effective implementation of e-RKAM. This research offers a substantive contribution to bridging the gap between educational digitalization policies and the institutional realities of private Islamic schools.